Reinventing Healthy Communities: Implications for Individual and Societal Well-Being (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
Contemporary views of "livable communities" maintain that density and diversity are good for cities. Healthy communities are more pedestrian-friendly and less automobile-centric. Mixed use zoning keeps a flow of people through parks, streets, neighborhoods, and districts, which is good for business, safety, and tourism. Dwellings are human scale and locally-sourced food is more sustainable for the environment and healthier for individuals. But how should social institutions collaborate with those of the economic and political sectors to maximize community well-being? The United Way partnership model and the growing concern for triple-bottom-line outcomes involving financial, social, and environmental considerations offer a broad perspective on healthy communities. This special collection, therefore, employs a wide lens to examine multiple factors that characterize healthy communities including inclusiveness, equity, human rights, and mutual assistance. Researchers from various fields including psychiatry, public health, sociology, political science, community planning, economics, kinesiology, and social work present their findings on critical issues impacting the health of communities.